Spectral theory of linear differential operators and comparison algebras - Cordes, H. O. 1925- (Cambridge University Press, 1987)
The main aim of this book is to introduce the reader to the concept of comparison algebra, defined as a type of C*-algebra of singular integral operators. The first part of the book develops the necessary elements of the spectral theory of differential operators as well as the basic properties of elliptic second order differential operators. The author then introduces comparison algebras and describes their theory in L2-spaces and L2-Soboler spaces, and in particular their importance in solving functional analytic problems involving differential operators. The book is based on lectures given in Sweden and the USA.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Differential operators; Linear operators; Spektraltheorie; Linearer Differentialoperator